Teaching Design Thinking in Marketing: Linking Product Design and Marketing Strategy in a Product Development Class. (December 2018) - Chen, Steven; Benedicktus, Ray; Kim, Yuna; Shih, Eric
Design thinking refers to the implementation of a firm's design philosophy into design processes and outputs. This article introduces two design thinking approaches—user-centered design and design-driven innovation—that frame product design activities and show how these approaches can be incorporated into marketing curricula. The aim of this article is to show how marketing educators can help students appreciate and understand the processes and consequences of developing new products using different design thinking approaches. First, an experiment is conducted to examine the effect of design thinking approaches (user-centered design, design-driven innovation) on design and marketing outcomes (perceived originality, perceived usefulness, and perceived value). Second, based on the results of the study, the article develops a step-by-step guide on how to execute a design thinking module in a product-oriented marketing course.